Public libraries as partners in youth development establishing youth programs and services in the Quezon City Public Libraries - Panti, Michelle F.; Faderon, Rosalie B.; Cruz, Ma. Divina P. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2004)
The purpose of the study was to determine the reading habits and leisure activities of the third and fourth year high schools students in Quezon City as well as their source of reading materials, their awareness of the existence of public libraries in Quezon City and find out who encourage and inspire them to visit the public libraries in Quezon City and to recommend after-school programs through youth programs and services in Quezon City public libraries. The descriptive survey method was used with the questionnaire as well as observation and interviews. The data gathered were tallied, tabulated and interpreted using frequencies and percentages.
The respondents were the selected third and fourth year students in Quezon City public high schools for the school year 2003-2004. Four hundred eighty students were given questionnaires and the librarians of Quezon City public libraries were interviewed. Results indicate that the youth are aware of the existence of public libraries in Quezon City. They visit the library frequently to read books for their homework. The respondents are very much interested in the creation of different youth programs and services in the Quezon city Public libraries. They are willing to participate, work and serve voluntarily in the public libraries even if they are engaged in different leisure activities. The youth services and programs that the respondents want to have in the QCPL are the following; "Reading Programs and Homework Assistance, Career Development Programs and Services, Cultural Programs, and Community Service and Leadership Programs. The youth are very much willing to offer their services for their fellow youth through recruitment, they would help in the set up and clean up before and after the program, they would make recommendations on program content and structure and could lead, facilitate and present the program.
The following are recommended: 1. After-school programs should be introduced as an effective way to fight youth-related crimes through the implementation of the different youth programs and services in the Quezon City Public Libraries (QCPL). Creation of network of youth services providers as key players in youth advocacy: librarians, youth, youth organizations parents, media, school administrators and teachers, library associations, non-government organizations and government organizations and government agencies and leaders. These key players provide the students an opportunity to develop their hidden potentials through encouragement and inspiration to visit public libraries, not only to read books and do their homework but also to voluntarily offer their services. Advocacy in youth development through public libraries' after-school youth programs and services should be initiated by the librarians in Quezon City Public libraries through the help of these key players. 2. Include youth services librarianship as one of the courses in the field of library and information science, so that proper training will be given to the students who want to have specialized training and work directly with the youth. 3. School library and public library cooperation and coordination should be established to firmly support the curriculum, promote reading and stress the role of libraries in youth development. Networking with academic libraries and other special libraries should also be established.
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Public libraries -- Philippines -- Quezon City; Youth -- Services for -- Philippines -- Quezon City